Treatment concepts for restorations of endodontically treated teeth: Survey of dentists in Jeddah city, Saudi Arabia - Mohammed Zahran; Mona El-Madhoun; Samaa Redwan; Khalid Merdad; Helal Sonbul; Dania Sabbahi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Practices followed by dentists for restoring endodontically treated teeth (ETT) vary with a variety of available techniques and materials for post- and-core restorations. The aim of this study was to identify concepts for restoring ETT among dentists in Jeddah, Saudi Arabia. Materials and Methods: A two-section questionnaire was developed using online web-based application (Google forms) and sent to 400 dentists. The first section collected demographic information and the second section concerned about the treatment concept and materials for restoring ETT. Descriptive statistics were used to analyze the data, followed by Chi-square or Fisher's exact test to compare the responses to different questions among general dentists and specialists/consultants. Results: A total of 138 questionnaires were completed. Most of the participants reported a frequently or always use of extracoronal restoration in anteriors (55.1%), premolars (89.1%) and 88.4% for molars. Participant reported frequent placement of posts in anteriors (56.5%), premolars (84.1%) and 64.5% for molars. Nonmetallic post and cast post and core were the preferred option for anteriors and molars, while responses were equally divided between nonmetallic post and cast post and core for premolars. Composite resin was the preferred core material for all teeth. Conclusions: The use of endodontic posts, composite resin as a core and extracoronal restoration for restoring ETT is common among participants. Some of the concepts expressed by the participants are outdated and does not coincide with the evidence-based practice.